How I manage patient with tinnitus? - Asma Abdullah; Yii Hern E; Norsyamimi AR; Kirubananthini J; Roslenda AR; Tuti Iryani MD; Noor Dina Hashim; Rosa Falerina; Zara Farina N; Khai Yng H (Oto Rhino Laryngologica Indonesiana, 2020)
ABSTRACTBackground: Tinnitus is believed to cause significant psychological distress leading to impairment in quality of life (QOL). Purpose: To assess the negative impact of tinnitus on patient’s QOL and discuss the management approach of tinnitus patient. Method: A cross-sectional study was conducted within one year duration on 88 patients who experienced tinnitus. Patients from Otorhinolaryngology clinic, Universiti Kebangsaan Malaysia Medical Centre (UKMMC) were evaluated based on socio-demographic data, clinical data and QOL. QOL was assessed using Tinnitus Handicap Inventory (THI), a self-report questionnaire measuring 3 domains of QOL: functional, emotional and catastrophic scales. Result: Respondents consisted of 35 males (39.8%) and 53 females (60.2%), with mean age of 57.9±13.9 years old. Pure tone audiometry should be done at least once during the follow up period. Patients with persistent tinnitus had significantly higher mean THI total scores (p=0.042) and emotional subscale score (p=0.037) compared to patients with intermittent tinnitus. However, there were no significant associations between gender, duration of tinnitus and laterality of tinnitus with patient’s THI score. Discussion: All patients should have good history taking, proper physical examination and investigation. Those without the primary cause of tinnitus would be given tinnitus activity treatment by good counselling on tinnitus. Patient with vascular disorder would be given conservative treatment. Conclusion: Magnetic resonance imaging was indicated in asymmetrical hearing loss with tinnitus. Computed tomography scan with contrast was indicated when there is pulsatile tinnitus with/without abnormal ear finding. Patients with high grades THI questionnaire would be referred to psychiatrist for further assessment. ABSTRAKLatar belakang: Tinitus diyakini dapat menyebabkan stress psikologi yang signifikan sehingga mengakibatkan penurunan kualitas hidup seseorang (Quality of Life / QOL). Tujuan: Menilai dampak negatif tinitus pada kualitas hidup penderita dan merencanakan penatalaksanaannya. Metode: Penelitian ini merupakan studi potong lintang pada 88 penderita tinitus selama satu tahun. Penderita yang datang ke unit rawat jalan Telinga Hidung Tenggorok Bedah Kepala dan Leher (THT-KL), Universiti Kebangsaan Malaysia Medical Centre (UKMMC) dilakukan evaluasi berdasarkan data demografi, data klinis dan QOL. Quality of life dinilai menggunakan Tinnitus Handicap Inventory (THI), kuesioner tentang penderita yang mengukur 3 domain QOL: skala fungsional, emosional dan katastropik. Hasil: Responden terdiri dari 35 laki-laki (39,8%) dan 53 perempuan (60,2%), dengan rerata usia 57.9±13.9 tahun. Audiometri nada murni perlu dilakukan minimal satu kali selama periode penelitian. Penderita dengan tinitus persisten secara signifikan memiliki nilai rata-rata THI yang lebih tinggi (p=0.042) dan nilai emotional subscale (p=0.037) dibandingkan dengan penderita tinitus intermiten. Tidak ada hubungan yang signifikan antara jenis kelamin, durasi tinitus dan lateralisasi tinitus dengan nilai THI penderita. Diskusi: Semua penderita diperlukan anamnesis yang baik dan pemeriksaan fisik yang menyeluruh. Penderita tanpa penyebab primer dari tinitusnya akan diberikan terapi konseling tinitus yang baik. Penderita dengan gangguan pembuluh darah akan diberikan pengobatan konservatif. Kesimpulan: Magnetic resonance imaging perlu dilakukan pada gangguan pendengaran satu sisi dengan tinitus. Computed tomography scan dengan kontras dilakukan pada tinitus pulsatil dengan atau tanpa kelainan pada telinga. Pada pendertita dengan nilai kuesioner THI yang tinggi akan dirujuk ke psikiater untuk penilaian lebih lanjut.